Textuality in feedback types of an adaptive hypermedia: a case study - Bazarim, Milene; Gonçalves, Adair Vieira; Fechus, Gustavo (Revista Letras Raras, 2021)
In this article, we present the results of a research that aimed to investigate how textuality is contemplated in the in the correction criteria and subcriteria of the opinion article genre adopted by an adaptive hypermedia. On such hypermedia, the proofreader uses digital tools which include several feedback types, including the controlled correction, which can we comprehended as a type of formative feedback. The analysis is based on the concepts of text and textuality criteria arising from Textual Linguistics, as well as on the concept of feedback as a text, a way of dialogue and a scaffold on which the student relies to rewrite his production. It is a qualitative research developed in the field of transdisciplinary studies of Applied Linguistics in which the case study is the dominant methodology. The results show that the hypermedia feedback types contemplate aspects of traditional grammar, structural characteristics of the textual genre and textuality criteria, especially cohesion. These results are relevant, because they point out that the use of digital tools in feedback practice may cause changes in the ways of thinking about and acting in the correction of school texts.